Soft magnetic metal particles, pressed powder cores and magnetic components

By forming a three-layer insulating film structure on soft magnetic metal particles, the problem of insufficient initial magnetic permeability μi of the pressure powder core in the prior art is solved, and higher magnetic properties are achieved.

CN119742142APending Publication Date: 2025-04-01TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411347640.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to provide a powdered magnetic core with high initial magnetic permeability μi, and the magnetic properties of soft magnetic metal particles need to be improved.

Method used

A soft magnetic metal particles having core particles and an insulating film are used, and the insulating film is composed of three layers: the first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

Benefits of technology

Through this structure, the initial magnetic permeability μi of the powdered magnetic core is significantly improved and the magnetic properties are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742142A_ABST
    Figure CN119742142A_ABST
Patent Text Reader

Abstract

The present invention relates to a soft magnetic metal particle, a powder magnetic core and a magnetic component. The soft magnetic metal particle comprises a core particle and an insulating film formed on the surface of the core particle. The insulating film comprises a first layer, a second layer and a third layer. The first layer is in contact with the surface of the core particle, and the second layer is in contact with the first layer and the third layer. The first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to soft magnetic metal particles, pressed powder magnetic core and magnetic components. Background Art

[0002] Patent Document 1 describes that the aspect ratio of flat powders is controlled and that an insulating coating covering the flat powders is composed of a polymer containing titanium alkoxide.

[0003] Patent Document 2 describes a magnetic material including soft magnetic alloy particles coated with various oxide films.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2015 / 033825

[0007] Patent Document 2: Japanese Patent Application Publication No. 2018-11043 Summary of the invention

[0008] Technical problem to be solved by the invention

[0009] One embodiment of the present invention provides a soft magnetic metal particle capable of providing a powder magnetic core having a high initial magnetic permeability μi.

[0010] Means for solving technical problems

[0011] The soft magnetic metal particles of one embodiment of the present invention have a core particle and an insulating film formed on the surface of the core particle, the insulating film has a first layer, a second layer and a third layer, the first layer is connected to the surface of the core particle, the second layer is connected to the first layer and the third layer, the first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

[0012] A powder magnetic core according to one embodiment of the present invention includes the above-mentioned soft magnetic metal particles.

[0013] A magnetic member according to one embodiment of the present invention includes the above-mentioned soft magnetic metal particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a schematic diagram of a cross section of a powder magnetic core according to one embodiment of the present invention.

[0015] Figure 2 TEM images and various mapping images of cross sections of soft magnetic metal particles.

[0016] Figure 3 For the general Figure 2An enlarged image of the insulating film periphery along the film thickness direction.

[0017] Explanation of symbols:

[0018] 1…Powder core

[0019] 11…Metallic magnetic particles (core particles)

[0020] 11a…Surface of metal magnetic particles

[0021] 12…Grain boundary phase

[0022] 13…Insulation film

[0023] 13a…First floor

[0024] 13b…Second floor

[0025] 13c…Third floor DETAILED DESCRIPTION

[0026] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The embodiments of the present invention described below are examples for illustrating the present invention. Various components involved in the embodiments of the present invention, such as numerical values, shapes, materials, manufacturing processes, etc., can be changed or altered within the scope that does not cause technical problems.

[0027] Furthermore, the shapes and the like shown in the drawings of the present invention do not necessarily correspond to the actual shapes and the like. This is because the shapes and the like may be changed for the purpose of explanation.

[0028] like Figure 1 As shown, a powder magnetic core 1 according to an embodiment of the present invention includes a metal magnetic particle (core particle) 11 and a grain boundary phase 12. It also includes an insulating film 13 formed on the surface 11a of the core particle 11. The insulating film 13 has a first layer 13a, a second layer 13b and a third layer 13c. The second layer 13b is in contact with the first layer 13a and the third layer 13c. The first layer 13a contains at least Fe. The second layer 13b contains at least Ti. The third layer 13c contains at least Si. In addition, the insulating film 13 may also have a layer different from the third layer 13c on the outside of the third layer 13c.

[0029] A soft magnetic metal particle according to an embodiment of the present invention comprises a core particle 11 and an insulating film 13 formed on a surface 11a of the core particle 11. The insulating film 13 comprises a first layer 13a, a second layer 13b and a third layer 13c. The second layer 13b is in contact with the first layer 13a and the third layer 13c. The first layer 13a contains at least Fe. The second layer 13b contains at least Ti. The third layer 13c contains at least Si. In addition, the insulating film 13 may also have a layer different from the third layer 13c on the outside of the third layer 13c.

[0030] The initial magnetic permeability μi of the powder magnetic core including the soft magnetic metal particles having the above-mentioned composition tends to become high.

[0031] The thickness of the insulating film 13 may be between 5 nm and 500 nm, or between 10 nm and 200 nm.

[0032] The thickness of the second layer 13b may be 1.0% to 75.0% or 2.0% to 50.0% relative to the thickness of the insulating film 13. When the thickness of the second layer 13b is 2.0% to 50.0% relative to the thickness of the insulating film 13, the initial magnetic permeability μi tends to be high.

[0033] The thickness of the first layer 13a is not particularly limited to the thickness of the insulating film 13. For example, it may be 10.0% to 35.0%. The thickness of the third layer 13c is not particularly limited to the thickness of the insulating film 13. For example, it may be 10.0% to 70.0%.

[0034] The thickness of each of the first layer 13a, the second layer 13b, and the third layer 13c is 0.7 nm or more. In other words, a layer having a thickness of less than 0.7 nm is not considered as the first layer 13a, the second layer 13b, or the third layer 13c.

[0035] The content of Fe in the first layer 13 a is not particularly limited. For example, the content ratio of Fe to the total content of Fe, Si, and Ti may be 50.0 at % or more and 95.0 at % or less.

[0036] The content of Ti in the second layer 13 b is not particularly limited. For example, the content ratio of Ti to the total content of Fe, Si, and Ti may be 1.0 at % or more and 10.0 at % or less.

[0037] The second layer 13b may also contain Si. Moreover, the content ratio of Ti in the second layer 13b to the total content of Si and Ti (hereinafter sometimes referred to as Ti / (Si+Ti)) may be 7.5 at% to 20.0 at%. When Ti / (Si+Ti) is 7.5 at% to 20.0 at%, the initial magnetic permeability μi tends to be high.

[0038] The content of Si in the third layer 13 c is not particularly limited. For example, the content ratio of Si to the total content of Fe, Si, and Ti may be 50.0 at % or more and 90.0 at % or less.

[0039] The third layer 13c may also contain Fe. Furthermore, the Ti / (Si+Ti) in the second layer 13b may be 7.5 at% to 20.0 at%, and the content ratio of Fe in the third layer 13c to the total content of Fe and Si (hereinafter sometimes referred to as Fe / (Si+Fe)) may be 10.0 at% to 50.0 at%. In this case, it is particularly easy to increase the initial magnetic permeability μi.

[0040] There is no particular limitation on how to include Fe in the first layer 13a. For example, as described later, when the core particle 11 includes Fe, an oxide of Fe may be included. When the core particle 11 includes Fe and other elements, an oxide of Fe and an oxide of other elements may be included, or a composite oxide of Fe and other elements may be included. In addition, the first layer 13a may include a compound other than an oxide containing Fe.

[0041] There is no particular limitation on how to include Ti in the second layer 13b. For example, a single substance of Ti may be dispersed in the second layer 13b. In addition, a compound containing Ti may be included in the second layer 13b. The type of the compound containing Ti is not particularly limited. For example, organic metal compounds containing Ti such as titanium alcoholate and titanate (metal complex with Ti as the central metal) may be cited. In addition, the compound containing Ti may be a simple oxide of Ti or a composite oxide of Ti and other elements. The second layer 13b may also include a composite oxide of Si and Ti.

[0042] The first layer 13a, the second layer 13b and / or the third layer 13c may also contain an oxide of Si. The type of the oxide of Si is not particularly limited. For example, it may be an Si-O series oxide (silicon oxide). In addition, the type of the Si-O series oxide is not particularly limited. For example, in addition to an oxide of Si such as SiO2, it may be a composite oxide containing Si and other elements.

[0043] The composition of the core particle 11 is not particularly limited as long as it contains a material exhibiting soft magnetism, and the core particle 11 may also contain Fe. When the core particle 11 contains Fe as a main component, the saturation magnetization is likely to become high. When the core particle 11 contains Fe and Si as main components, the initial magnetic permeability μi is likely to become high. When the core particle 11 contains Fe and Ni as main components, the initial magnetic permeability μi is likely to become high. When the core particle 11 contains Fe and Co as main components, the initial magnetic permeability μi is likely to become high.

[0044] It should be noted that “containing… as a main component” means that the content ratio of each element contained as the main component is more than 1 weight%, the total content ratio of the elements contained as the main component is more than 40 weight%, and the content ratio of each element other than the element contained as the main component is lower than the content ratio of the element with the lowest content ratio among the elements contained as the main component.

[0045] When the core particle 11 contains Fe as a main component, the content ratio of Fe is 40 weight % or more, and the content ratio of each element other than Fe is lower than the content ratio of Fe. It should be noted that the types of components other than the main component in the core particle 11 are not particularly limited. As the types of components other than the main component (Fe), for example, Ni, Co, Si, Zr, V, etc. can be cited.

[0046] In the case where the core particle 11 contains Fe and Si as main components, the content ratio of Fe is 1 weight % or more, the content ratio of Si is 1 weight % or more, the total content ratio of Fe and Si is 40 weight % or more, and the content ratio of each element other than Fe and Si is lower than the content ratio of the element with a lower content ratio in Fe and Si. It should be noted that the types of components other than the main components in the core particle 11 are not particularly limited. As the types of components other than the main components (Fe and Si), for example, Ni, Co, Zr, V, etc. can be cited.

[0047] When the core particles 11 contain Fe as the main component or contain Fe and Si as the main components, the content ratio of Fe and Si in the core particles 11 is not particularly limited. In terms of weight ratio, Si / Fe may be 0 / 100 to 20 / 80. When Si / Fe is 0 / 100 to 10 / 90 in terms of weight ratio, the saturation magnetization tends to be high.

[0048] In the case where the core particle 11 contains Fe and Ni as main components, the content ratio of Fe is 1% by weight or more, the content ratio of Ni is 1% by weight or more, the total content ratio of Fe and Ni is 40% by weight or more, and the content ratio of each element other than Fe and Ni is lower than the content ratio of the element with a lower content ratio in Fe and Ni. It should be noted that there is no particular limitation on the types of components other than the main components in the core particle 11. As the types of components other than the main components (Fe and Ni), for example, Co, Si, Zr, V, etc. can be cited.

[0049] When the core particle 11 contains Fe as a main component or contains Fe and Ni as main components, there is no particular limitation on the content ratio of Fe and Ni in the core particle 11. In terms of weight ratio, Ni / Fe may be 0 / 100 to 75 / 25.

[0050] When the core particle 11 contains Fe and Co as main components, the content ratio of Fe is 1 weight % or more, the content ratio of Co is 1 weight % or more, the total content ratio of Fe and Co is 40 weight % or more, and the content ratio of each element other than Fe and Co is lower than the content ratio of the element with a lower content ratio in Fe and Co. It should be noted that the types of components other than the main components in the core particle 11 are not particularly limited. As the types of components other than the main components (Fe and Co), Ni, Si, Zr, V, etc. can be cited.

[0051] When the core particle 11 contains Fe as a main component or contains Fe and Co as main components, the content ratio of Fe and Co in the core particle 11 is not particularly limited. In terms of weight ratio, Co / Fe may be 0 / 100 to 50 / 50.

[0052] The insulating film 13 does not need to cover the entire surface 11 a of the core particle 11 , but only needs to cover 90% or more of the entire surface 11 a of the core particle 11 .

[0053] The insulating film 13 is directly formed on the surface of the core particle 11 . That is, the surface 11 a of the core particle 11 is in contact with the insulating film 13 .

[0054] In addition to Fe and Ti, the insulating film 13 may also contain metal elements other than Fe and Ti. For example, Ba, Ca, Mg, Al, Zr, Ni, Mn, Zn, etc., whose oxides have insulating properties, can be cited. Among them, Ca, Mg, Zr, Ni, Mn, and Zn are relatively easy to introduce into the insulating film. The content of metal elements other than Fe and Ti is not particularly limited. For example, the content ratio relative to the total content of Fe and Ti can be 1 mol% or less.

[0055] There is no particular limitation on the method of determining whether the insulating film 13 has the first layer 13a, the second layer 13b, and the third layer 13c. The determination can be made using SEM-EDS, STEM-EDS, TEM-EDS, or the like.

[0056] For example, a TEM image of a cross section of a soft magnetic metal particle and mapping images of Fe, Ti, Si, and O prepared by TEM-EDS are shown in FIG. Figure 2 . Figure 2 The bright field portion of the lower side of the TEM image corresponds to Figure 1 The portion of the field of view darker than the core particle 11 corresponds to Figure 1 portion of the insulating film 13.

[0057] Further, Figure 2 An enlarged image of the periphery of the insulating film 13 along the film thickness direction is shown in Figure 3 .Depend on Figure 2 , Figure 3 It can be seen from each mapping image that Fe is mostly contained in the first layer 13a and the second layer 13b of the insulating film 13. It can be seen that Ti is mostly contained in the second layer 13b of the insulating film 13. It can be seen that Si is most contained in the third layer 13c of the insulating film 13, and the second most contained in the first layer 13a. It can be seen that O is contained in large quantities in the first layer 13a to the third layer 13c. That is, through TEM-EDS, it can be seen that the insulating layer 13 has a first layer 13a containing at least Fe, a second layer 13b containing at least Ti, and a third layer 13c containing at least Si.

[0058] An example of a method for measuring the thickness of the insulating film 13 and the thickness of each layer will be described below. However, the method for measuring the thickness of the insulating film 13 and the thickness of each layer is not limited to the method described below.

[0059] The thickness of the insulating film 13 can be measured by TEM imaging. The magnification of the TEM imaging is not particularly limited as long as it is a magnification that can confirm the thickness of the insulating film 13. For example, it can be 100,000 to 500,000 times.

[0060] The position of the second layer 13b in the insulating film 13 can be confirmed by performing a line analysis of Ti by TEM-EDS. Specifically, firstly, a line analysis of the film thickness direction of the insulating film 13 is performed by TEM-EDS. Next, for the obtained signal intensity, the baseline is removed to determine the peak value of the signal intensity. Then, the signal intensity at the peak value is taken as 100%, and the portion with a signal intensity of more than 20% is set as the second layer 13b. Then, the portion of the insulating film 13 that is closer to the core particle 11 than the second layer 13b is set as the first layer 13a, and the portion of the insulating film 13 that is farther away from the core particle 11 than the second layer 13b is set as the third layer 13c.

[0061] The thickness of each layer can be confirmed from the position of each layer determined by the above method.

[0062] The method for measuring the composition of each layer is not particularly limited. For example, a sufficient number of measurement sites may be provided in each layer, and the composition of each measurement site may be calculated using EDS and averaged to thereby measure the composition of each layer.

[0063] The soft magnetic metal particles contained in the powder magnetic core 1 contain grain boundary phases 12 between each other. The type of compound contained in the grain boundary phase 12 is not particularly limited. For example, it can be a silicone resin, an epoxy resin, an imide resin and / or an Si-O oxide. In addition, the grain boundary phase 12 can also contain voids. As the silicone resin that can be contained in the grain boundary phase 12, for example, a methyl silicone resin can be mentioned. As the epoxy resin, for example, cresol novolac can be mentioned. As the imide resin, for example, bismaleimide can be mentioned.

[0064] It should be noted that, by the heat treatment described later, part or all of the silicone resin contained in the grain boundary phase 12 may be modified into Si—O-based oxides such as SiO 2 .

[0065] The content of the core particles 11 and the content of the compound contained in the grain boundary phase 12 are not particularly limited. The content of the core particles 11 in the entire powder magnetic core 1 can be 90 wt% to 99.9 wt%. The content of the compound contained in the grain boundary phase 12 in the entire powder magnetic core 1 can be 0.1 wt% to 10 wt%.

[0066] The method of observing the cross section of the powder core 1 is not particularly limited. For example, the powder core 1 can be observed at an appropriate magnification using SEM, STEM, or TEM. Furthermore, the composition of each part of the powder core 1 can be measured by performing EDS analysis.

[0067] The method for manufacturing the powder magnetic core 1 of the present embodiment is as follows, but the method for manufacturing the powder magnetic core 1 is not limited to the method described below.

[0068] First, prepare the core particles 11. There is no particular limitation on the method for preparing the core particles 11, and examples thereof include gas atomization and water atomization. There are no particular limitations on the particle size and roundness of the core particles 11. When the median value (D50) of the particle size is 1 μm to 100 μm, the initial magnetic permeability μi tends to become higher. The roundness of the core particles 11 can be, for example, greater than 0.5 and less than 1, or greater than 0.7 and less than 1, or greater than 0.8 and less than 1.

[0069] Next, the insulating film 13 is formed on the surface 11 a of the core particle 11 .

[0070] First, a first layer 13a is formed on the surface 11a of the core particle 11. There is no particular limitation on the method for forming the first layer 13a. In the case where the core particle 11 contains Fe, the first layer 13a can also be formed by oxidizing the surface of the core particle 11. There is no particular limitation on the method for oxidizing the surface of the core particle 11. For example, heat treatment can be performed in an oxygen-containing atmosphere. The thickness of the first layer 13a can be controlled by appropriately adjusting the oxygen concentration in the atmosphere, the heat treatment temperature, and the heat treatment time.

[0071] Alternatively, the first layer 13 a containing Fe may be formed by applying a coating solution containing Fe onto the core particles 11 for coating.

[0072] Next, the second layer 13b is formed on the surface of the first layer 13a. There is no particular limitation on the method of forming the second layer 13b. For example, a method of applying a coating solution containing alkoxysilane and Ti to the core particle 11 can be cited. It should be noted that, in the case where Si is not contained in the second layer 13b, alkoxysilane can be contained in the coating solution. There is no particular limitation on the method of applying the coating solution to the core particle 11, and a method such as spray diffusion can be cited. There is no particular limitation on the state in which Ti is contained in the coating solution. For example, Ti can be contained in the form of titanium alcoholate, or in the form of titanate. In the case where Ti is contained in the form of titanate or titanium alcoholate and the heat treatment of the powder compact described later is performed, the titanate or titanium alcoholate decomposes due to the heat treatment. The following describes the case where titanium alcoholate is added to the coating solution.

[0073] The concentration of alkoxysilane, the concentration of titanium alkoxide and the type of solvent in the coating solution are not particularly limited. The concentration of alkoxysilane and the concentration of titanium alkoxide can be determined according to the target Ti / (Si+Ti) value, the target film thickness of the insulating film 13 and the like.

[0074] As alkoxysilane, monoalkoxysilane, dialkoxysilane, trialkoxysilane, tetraalkoxysilane can be mentioned. As monoalkoxysilane, trimethylmethoxysilane, trimethylethoxysilane, trimethyl (phenoxy) silane etc. can be mentioned. As dialkoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, diisobutyldimethoxysilane, tert-butylmethyldimethoxysilane, tert-butylmethyldiethoxysilane etc. can be mentioned. As trialkoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane, n-propyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, phenyltrimethoxysilane etc. can be mentioned. As tetraalkoxysilane, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane etc. can be mentioned. As the alkoxysilane, one kind of alkoxysilane may be used, or two or more kinds of alkoxysilanes may be used in combination.

[0075] Examples of titanium alkoxide include titanium tetramethoxide, titanium tetraethoxide, titanium tetra-n-propoxide, titanium tetraisopropoxide, and titanium tetra-n-butoxide. As titanium alkoxide, one titanium alkoxide may be used, or two or more titanium alkoxides may be used in combination. From the perspective of ease of acquisition, the titanium alkoxide may be titanium tetraethoxide or titanium tetra-n-butoxide.

[0076] Examples of the solvent include water, ethanol, and isopropanol.

[0077] In addition, during the spray diffusion, the ratio of alkoxysilane to the total amount of the core particles 11 may be 0.1 wt % to 5 wt %. In addition, the more alkoxysilane is present, the thicker the second layer 13 b tends to be.

[0078] The conditions for the spray diffusion are not particularly limited, but the spray diffusion is carried out while performing a heat treatment at a temperature of 50° C. to 90° C., so that the sol-gel reaction for forming the second layer 13 b can be easily promoted.

[0079] After the core particles 11 are dried and the solvent is removed after the coating solution is sprayed and diffused, they are heated at 200°C to 400°C for 1 to 10 hours to perform a sol-gel reaction to form the second layer 13b. The higher the heating temperature and the longer the heating time, the higher the density of the second layer 13b tends to be.

[0080] The case of adding titanate to the coating solution is the same as the case of adding titanium alcoholate to the coating solution, except that the above-mentioned titanium alcoholate is replaced by titanate. Examples of the titanate include titanium acetylacetonate, titanium tetraacetylacetonate, titanium ethyl acetoacetate, titanium octanediolate, titanium lactate, titanium triethanolamine, titanium diethanolamine, etc. As the titanate, one titanate may be used, or two or more titanates may be used in combination.

[0081] Next, the third layer 13c is formed on the surface of the second layer 13b. The method for forming the third layer 13c is not particularly limited. For example, a method of applying a coating solution containing alkoxysilane to the core particle 11 can be cited. The method of applying the coating solution to the core particle 11 is not particularly limited, and a method such as spray diffusion can be cited. The type of alkoxysilane is not particularly limited, and the above-mentioned types of alkoxysilane can be used. The type of solvent is not particularly limited, and the above-mentioned types of solvent can be used.

[0082] In addition, during the spray diffusion, the ratio of alkoxysilane to the total amount of the core particles 11 may be 0.1 wt % to 5 wt %. In addition, the more alkoxysilane is present, the thicker the third layer 13 c tends to be.

[0083] The conditions for the spray diffusion are not particularly limited, but the spray diffusion is carried out while performing a heat treatment at a temperature of 50° C. to 90° C., so that the sol-gel reaction for forming the third layer 13 c can be easily promoted.

[0084] After the core particles 11 are dried and the solvent is removed after spraying the coating solution, they are heated at 200°C to 400°C for 1 to 10 hours to perform a sol-gel reaction to form the third layer 13c. The higher the heating temperature and the longer the heating time, the higher the density of the third layer 13c tends to be.

[0085] There is no particular limitation on the method of making the third layer 13c contain Fe. For example, a compound containing Fe may be further added to the coating solution. Examples of the compound containing Fe include ferric acetate, ferric chloride, and ferric sulfate.

[0086] The concentration of the alkoxysilane in the coating solution, the concentration of the Fe-containing compound, and the type of solvent are not particularly limited. The concentration of the alkoxysilane and the concentration of the Fe-containing compound can be determined based on the target Fe / (Si+Fe) value, the target film thickness of the third layer 13c, etc.

[0087] Next, in the case where the grain boundary phase 12 in the powder compact before the heat treatment described later contains a resin, a resin solution is prepared. In addition to the above-mentioned silicone resin, epoxy resin and / or imide resin, a curing agent may be added to the resin solution. The type of curing agent is not particularly limited, and examples thereof include epichlorohydrin. In addition, the solvent of the resin solution is not particularly limited, and may be a volatile solvent. For example, acetone, ethanol, etc. may be used. In addition, when the resin solution as a whole is set to 100% by weight, the total concentration of the resin and the curing agent may be set to 10 to 80% by weight.

[0088] Next, the core particles 11 formed with the insulating film 13 are mixed with a resin solution. That is, the soft magnetic metal particles are mixed with the resin solution. Then, the solvent of the resin solution is volatilized to obtain particles. The obtained particles can be directly filled into a mold or filled into a mold after granulation. There is no particular limitation on the granulation method during granulation, for example, a sieve with a mesh size of 45 to 500 μm can be used.

[0089] Next, the obtained particles are filled into a mold of a specified shape and pressed to obtain a powder compact. The pressure during pressing (molding pressure) is not particularly limited, and can be set to 500 to 1500 MPa, for example. The higher the molding pressure, the higher the initial magnetic permeability μi of the powder core 1 finally obtained.

[0090] Comparing the case where the insulating film 13 has all the first to third layers 13a to 13c with the case where it does not have any one or more layers, it can be seen that even if the molding pressure is the same, the initial magnetic permeability μi of the powder core 1 is higher when the insulating film 13 has all the first to third layers 13a to 13c.

[0091] The produced compressed powder body can also be used as a powder core. In addition, the produced compressed powder body can also be heat-treated, and the sintered body produced by the heat treatment can be used as a powder core. The conditions of the heat treatment are not particularly limited. In the case where a silicone resin is used as the resin, the heat treatment can be carried out under the conditions of sintering the silicone resin. For example, the heat treatment can be carried out at a temperature of 400°C to 1000°C for 0.1 hours to 10 hours. In addition, the atmosphere during the heat treatment is not particularly limited, and the heat treatment can be carried out in the air or in a nitrogen atmosphere.

[0092] When the pressed powder contains titanate or titanium alkoxide, part or all of the titanate or titanium alkoxide can be decomposed by the above heat treatment. In particular, titanate can be completely decomposed by heat treatment at 700°C to 1000°C. That is, by heat treatment at 700°C to 1000°C, titanate can be excluded from the sintered body.

[0093] As described above, the dust magnetic core and the method for manufacturing the same according to the present embodiment have been described, but the dust magnetic core and the method for manufacturing the same according to the present invention are not limited to the above-described embodiment.

[0094] In addition, the use of the powder magnetic core of the present invention is not particularly limited. For example, it can be used as a magnetic component such as an inductor, a reactor, a choke coil, and a transformer. The magnetic component of the present invention includes the above-mentioned powder magnetic core.

[0095] Example

[0096] The present invention will be described below based on more detailed examples, but the present invention is not limited to these examples.

[0097] As metal magnetic particles (core particles), Fe-Si alloy particles (alloy particles containing Fe and Si as main components) were prepared by gas atomization method, wherein the weight ratio of Si / Fe was 4.5 / 95.5 and the total amount of Fe and Si was 99 weight % or more. It should be noted that the median particle size (D50) of the Fe-Si alloy particles was 30 μm and the roundness was about 0.90.

[0098] First, a first layer is formed on the surface of the metal magnetic particles. The first layer is formed by oxidizing the surface of the metal magnetic particles. Specifically, the first layer is formed by heat treating the metal magnetic particles at 800°C in a nitrogen atmosphere with an adjusted oxygen concentration. The oxygen concentration and the heat treatment time are set so that the film thickness of the first layer becomes the value shown in Tables 1 to 4. The oxygen concentration is set to 0.1 to 1.0%, and the heat treatment time is set to 1 to 10 hours.

[0099] Next, coating solutions for forming the second layer and the third layer are prepared.

[0100] The coating solution for forming the second layer (hereinafter sometimes referred to as the coating solution for the second layer) is prepared by mixing 15 parts by weight of ethanol, trimethoxysilane, titanium tetra-n-butoxide, and 2.0 parts by weight of pure water, with the total amount of the above-mentioned metal magnetic particles being 100 parts by weight. The ratio of trimethoxysilane to titanium tetra-n-butoxide is set so that Ti / (Si+Ti) in the second layer of the insulating film finally obtained becomes the value shown in Tables 1 to 4. In addition, the total amount of trimethoxysilane and titanium tetra-n-butoxide is set so that the film thickness of the second layer finally obtained becomes the value shown in Tables 1 to 4.

[0101] The coating solution for forming the third layer (hereinafter sometimes referred to as the coating solution for the third layer) is prepared by mixing 15 parts by weight of ethanol, trimethoxysilane, and an aqueous solution of ferric acetate with respect to 100 parts by weight of the total amount of the above-mentioned metal magnetic particles. The ratio of trimethoxysilane to the aqueous solution of ferric acetate and the concentration of the aqueous solution of ferric acetate are set in such a way that the Fe / (Si+Fe) in the third layer of the insulating film finally obtained becomes the values ​​shown in Tables 1 to 4. In the samples described in Tables 1 to 3, pure water may be appropriately mixed instead of the aqueous solution of ferric acetate. In addition, the total amount of trimethoxysilane and the aqueous solution of ferric acetate or pure water is set in such a way that the film thickness of the third layer finally obtained becomes the values ​​shown in Tables 1 to 4.

[0102] In each example other than Comparative Example 1, a second layer is formed on the surface of the first layer. The metal magnetic particles formed with the first layer are mixed with the coating solution for the second layer, and heat-treated while being sprayed and diffused. The heat treatment temperature is set to 80°C, and the heat treatment time is set to 1 hour. Furthermore, by drying after the heat treatment, metal magnetic particles having the second layer formed on the surface of the first layer are obtained. It should be noted that in Comparative Example 1 in Table 1, the second layer is not formed.

[0103] Next, in each example other than Comparative Example 1, a third layer was formed on the surface of the second layer. The metal magnetic particles formed with the first layer and the second layer were mixed with the coating solution for the third layer, and heat-treated while being sprayed and diffused. The heat treatment temperature was set to 80° C., and the heat treatment time was set to 1 hour. Further, drying was performed after the heat treatment, thereby obtaining metal magnetic particles with the third layer formed on the surface of the second layer.

[0104] In Comparative Example 1, a third layer was formed on the surface of the first layer. The metal magnetic particles formed with the first layer were mixed with the coating solution for the third layer and heat-treated while being sprayed and diffused. The heat treatment temperature was set to 80° C. and the heat treatment time was set to 1 hour. After the heat treatment, the particles were dried to obtain metal magnetic particles having the third layer formed on the surface of the first layer.

[0105] The obtained metal magnetic particles were passed through a 140-mesh screen and then heat treated at a temperature of 300° C. and a time of 5 hours.

[0106] Next, a silicone resin and acetone were mixed to prepare a resin solution. As the silicone resin, Shin-Etsu Silicone KR-242A (manufactured by Shin-Etsu Chemical Co., Ltd.) was used. The silicone resin and acetone were mixed at a weight ratio of 34:66.

[0107] The total amount of the metal magnetic particles was 100 parts by weight, and 6 parts by weight of the resin solution was added and mixed. Then, the mixture was dried to volatilize the acetone, and particles were obtained. Then, the particles were sized by passing through a 42-mesh sieve. The obtained particles were dried on a hot plate at 50°C for 0.5 hours to prepare granulated powder.

[0108] 0.1 parts by weight of zinc stearate was added to 100 parts by weight of granulated powder, and the resultant was molded to obtain an annular iron core. The filling amount of granulated powder was set to 5 g. The molding pressure was appropriately adjusted so that the density of the final annular pressed powder magnetic core was 6.4 g / cm 3 The shape of the mold was set to a ring with an outer diameter of Φ17.5 mm, an inner diameter of Φ10.0 mm, and a thickness of 4.8 mm.

[0109] The obtained annular core was heat treated at 700°C for 1 hour to obtain an annular powder magnetic core. The powder magnetic core finally obtained as a whole accounted for 100% by weight, and the metal magnetic particles accounted for about 98% by weight.

[0110] It was confirmed by TEM-EDS observation that the insulating film in each example includes the first layer to the third layer, and that the insulating film in Comparative Example 1 includes only the first layer and the third layer.

[0111] In each embodiment, the film thickness of the insulating film is measured by TEM images, and the position of the second layer is determined by line analysis of TEM-EDS observation. The film thickness of the second layer is determined by the position of the second layer. The portion of the insulating film that is closer to the inner side than the second layer, that is, the portion closer to the core particle, is regarded as the first layer, and the film thickness of the first layer is determined. The portion of the insulating film that is closer to the outer side than the second layer, that is, the portion farther from the core particle, is regarded as the third layer, and the film thickness of the third layer is determined.

[0112] The film thickness of the insulating film was specifically measured by measuring the total thickness of the layer in the field of view darker than the metal magnetic particles in the TEM image.

[0113] Next, Ti / (Si+Ti) in the second layer was quantitatively measured by EDS. Ten measurement sites were set in the second layer, and the Ti / (Si+Ti) at each measurement site was averaged. The results are shown in Tables 1 to 4.

[0114] Next, Fe / (Si+Fe) in the third layer was quantitatively measured by EDS. In the third layer, 10 measurement sites were set, and the Fe / (Si+Fe) at each measurement site was averaged. The results are shown in Tables 1 to 4.

[0115] In Comparative Example 1, the first layer and the third layer were distinguished by TEM-EDS line analysis. Composition analysis was performed on C, O, Si, Fe, and Ti, and the portion with an Fe concentration of 50 at% or more was determined to be the first layer, and the portion with an Si concentration of 20 at% or more was determined to be the third layer. Then, based on the distinction results, the film thickness of each layer was measured. The results are shown in Table 1.

[0116] The initial magnetic permeability μi of the annular powder core was measured by winding a wire around the annular powder core for 50 turns using an LCR tester (LCR428A from HP). For the initial magnetic permeability μi, 40.0 or more and less than 45.0 was set as good, 45.0 or more and less than 50.0 was set as better, 50.0 or more and less than 55.0 was set as further good, and 55.0 or more was set as the best.

[0117] The density of the annular powder core was calculated from the size and weight of the obtained powder core. It was confirmed that the density of the annular powder core was 6.4 g / cm 3 about.

[0118] [Table 1]

[0119]

[0120] [Table 2]

[0121]

[0122] [Table 3]

[0123]

[0124] [Table 4]

[0125]

[0126] According to Table 1, when the film thickness of the insulating film and the density of the annular powder core are made substantially the same, the initial magnetic permeability μi of Examples 1a and 1 to 10 including all the first to third layers is better than that of Comparative Example 1 in which the insulating film does not contain the second layer. The initial magnetic permeability μi of Examples 1 to 9 in which the film thickness of the second layer is 2.0% to 50.0% relative to the film thickness of the insulating film is better than that of Examples 1a and 10 in which the film thickness of the second layer is less than 2.0% or more than 50.0% relative to the film thickness of the insulating film.

[0127] According to Table 2, even if the film thickness of the insulating film is changed from Example 4 in Table 1, the initial magnetic permeability μi is good.

[0128] Examples 17 to 24 in Table 3 are examples in which the Ti / (Si+Ti) of the second layer is changed from Example 4 in Table 1. Examples 18 to 23 in which the Ti / (Si+Ti) of the second layer is 7.5 at% or more and 20.0 at% or less have better initial magnetic permeability μi than Examples 4, 17, and 24 in which the Ti / (Si+Ti) of the second layer is less than 7.5 at% or more than 20.0 at%.

[0129] Examples 25a, 25 to 30 in Table 4 are examples in which the Fe / (Si+Fe) of the third layer is changed from Example 21 in Table 3. Sample Nos. 25 to 29 in which the Fe / (Si+Fe) of the third layer is 10.0 at% to 50.0 at% have better initial magnetic permeability μi than Examples 21, 25a, and 30 in which the Fe / (Si+Fe) of the third layer is less than 10.0 at% or more than 50.0 at%.

[0130] The technology of the present invention includes the following configuration examples, but is not limited thereto.

[0131] A soft magnetic metal particle in one configuration example of the present invention comprises a core particle and an insulating film formed on the surface of the core particle, wherein the insulating film comprises a first layer, a second layer and a third layer, wherein the first layer is in contact with the surface of the core particle, the second layer is in contact with the first layer and the third layer, the first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

[0132] In the soft magnetic metal particle, the thickness of the second layer may be 2.0% to 50.0% relative to the thickness of the insulating film.

[0133] In any of the soft magnetic metal particles described above, the second layer may further contain Si, and the content ratio of Ti in the second layer to the total content of Si and Ti may be 7.5 at % to 20.0 at %.

[0134] In any of the soft magnetic metal particles described above, the third layer may further contain Fe, and the content ratio of Fe in the third layer to the total content of Fe and Si may be 10.0 at % to 50.0 at %.

[0135] In any of the above-mentioned soft magnetic metal particles, the core particle may contain Fe.

[0136] In any of the above-mentioned soft magnetic metal particles, the thickness of the insulating film may be greater than or equal to 10 nm and less than or equal to 200 nm.

[0137] A powder magnetic core according to one structural example of the present invention includes any one of the soft magnetic metal particles described above.

[0138] A magnetic member according to one structural example of the present invention includes any one of the soft magnetic metal particles described above.

Claims

1. A soft magnetic metal particle, wherein: having a core particle and an insulating film formed on a surface of the core particle, The insulating film has a first layer, a second layer and a third layer, The first layer is in contact with the surface of the core particle, and the second layer is in contact with the first layer and the third layer. The first layer contains at least Fe, the second layer contains at least Ti, and the third layer contains at least Si.

2. The soft magnetic metal particles according to claim 1, wherein The thickness of the second layer is not less than 2.0% and not more than 50.0% of the thickness of the insulating film.

3. The soft magnetic metal particles according to claim 2, wherein The second layer further contains Si, and a content ratio of Ti in the second layer to a total content of Si and Ti is 7.5 at % or more and 20.0 at % or less.

4. The soft magnetic metal particles according to claim 3, wherein The third layer further contains Fe, and the content ratio of Fe in the third layer to the total content of Fe and Si is 10.0 at % or more and 50.0 at % or less.

5. The soft magnetic metal particle according to any one of claims 1 to 4, wherein The core particles contain Fe.

6. The soft magnetic metal particle according to any one of claims 1 to 4, wherein The thickness of the insulating film is greater than or equal to 10 nm and less than or equal to 200 nm.

7. A powder magnetic core, wherein: The invention comprises the soft magnetic metal particles according to any one of claims 1 to 6.

8. A magnetic component, wherein: The invention comprises the soft magnetic metal particles according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Magnetic material and electronic component

    JP2018011043A

  • Insulator-coated powder for magnetic member

    WO2015033825A1